An Unique Concentrated & Fermented Dosage Form of Pravahi kwatha - Vyas, Manish (International Journal of Pharmaceutical & Biological Archive, 2010)
Concentrated and fermented formulation is a new modified dosage form prepared by concentrating one of the basic formulations of Ayurveda, i.e. decoction. Due to its increased palatability & stability most of the pharmacies have started marketing these types of dosage form in place of decoction. Brihatpanchamoola was selected as basic raw materials for the preparation of same formulation. It includes roots of five trees i.e. Aegle marmelos Carr. (Rutaceae), Clerodendrum phlomidis Linn. (Verbenaceae), Oroxylum indicum Vent. (Bignoniaceae), Gmelina arborea Roxb. (Verbenaceae), Stereospermum suaveolens DC. (Bignoniaceae). Five batches were prepared to develop the SMP. Pravahi Kwatha (concentrated and fermented decoction) pH (4.63), viscosity (1.36 millipose), alcohol content (6.46) and total sugar (4.7). The decoction and its new dosage form were prepared from the same raw materials and compared analytically. . HPTLC profile shows that relatively more constituents are extracted in decoction from raw drug whereas they decrease when the concentrated dosage form is prepared from same decoction.